Improving Students’ Creative Thinking Skill in Mathematics through PBL Based on Catur Pramana by Controlling Students’ Numeric Skill - I Made Ego Teja Buana; I Gede Astawan (Jurnal Ilmiah Sekolah Dasar, 2020)
The Low Learning Thinking of students in learning Mathematics becomes a major problem in this research. This is caused by the learning model used which is incorrect and less varied. This study analyzed the influence of Problem Based Learning (PBL) models based on Catur Pramana on critical thinking skills with numerical ability control. This research was a quasi-experimental, with Posttest Only Control Group Design. The population in this study were all fifth-grade elementary schools with 177 students. The data collection method was done by using multiple-choice tests and essay tests. The data obtained were analyzed using the ANAKOVA test (covariance analysis) with the help of SPSS 20.0 for windows. The results of this study are significant results of the Problem Based Learning Model (PBL) based on Catur Pramana on critical thinking skills with Fcount 29,219 with sig; = 0,000 <0.05, there is a significant effect of Problem Based Learning (PBL) model based on Catur Pramana on mathematical thinking skills after obtaining numerical ability of students who obtain Fcount 9,398 with sig. = 0.004 <0.05; and are considered significant who have numerical ability to critical thinking skills of 35.05%. Based on these findings, it can be concluded that the Problem Based Learning Model based on Catur Pramana proves positive and there is a contribution of numerical ability to the critical thinking ability of Mathematics students.